RESEARCH OF ALGORITHMS AND EQUIPMENT FOR MOVEMENT OF MOBILE ROBOTS USING COMPUTER SIMULATION - Михайлов, Євген; Лінгур, Валерій; Антихович, Дмитро; Василенко, Олексій (Modern engineering and innovative technologies, 2023)
An analysis was made of existing means of moving mobile robots, which can be used to develop algorithms for controlling the movement of the robot. The possibilities of computer modeling for studying the algorithms and equipment of the means of movement of